Expression analysis of thaumatin-like proteins from Bursaphelenchus xylophilus and Pinus massoniana. (December 2017) - Meng, Fan-Li; Wang, Ju; Wang, Xuan; Li, Yong-Xia; Zhang, Xing-Yao
Abstract: The pine wood nematode Bursaphelenchus xylophilus has caused enormous economic losses in forests of many countries in the world. Many scientists have studied this disease, but the pathogenesis is still not fully understood. Our previous study showed that the thaumatin-like protein of B. xylophilus (Bx-TLP-1) was most similar to that of western white pine (TLP-S3:ADB97933.1 ) in structure and homology. To further explore the role of the thaumatin-like protein in the interaction of B. xylophilus with host pine, we cloned gene that encodes the thaumatin-like protein from Pinus massoniana, named Pm-tlp (gene accession number:KM063439 ). The deduced protein contains 180 amino acids, including 10 conserved cysteine residues. We also analyzed the expression of the two proteins from pine wood nematode and pine (roots, stems and needles) after inoculation with B. xylophilus . We found that over a month, the peaks of Bx-tlp-1 expression alternated with those of Pm-tlp . Furthermore, the first Bx-tlp-1 expression peak was earlier than Pm-tlp expression in stems and needles. In addition, we found that the α-pinene content corresponded with the expression of Bx-tlp-1 and Pm-tlp expression over the evaluated time course. The results showed that Bx-tlp-1 may interfere with the expression of Pm-tlp and the defense system to achieve its parasitism in the host, which may further influence the pinene content. These results provide information for further study of the function of thaumatin-like proteins in the interaction of B. xylophilus with P. massoniana. Highlights: TLP gene from Bursaphelenchus xylophilus ( Bx-tlp-1 ) was resembled to that from Pinus massoniana ( Pm-tlp ) in the structure and homology. There was a relationship between the pinene content and the expression patterns of Bx-tlp-1 and Pm-tlp. TLPs of B. xylophilus may disrupt or simulate the defense system and lead to metabolic disturbance of the host.